Molecular Characterization of a cDNA Encoding Slc11A1 (Nramp1) of Native Thai Cattle - Boonyaprakob, Ukadej; Homsavart , Sommai (Agriculture and Natural Resources, 2014)
Solute carrier family 11 member A1 (Slc11a1) is a candidate gene associated with resistance to intracellular pathogens. The complimentary DNA (cDNA) encoding the complete Slc11a1 protein was cloned and sequenced from 10 individuals in two breeds of Thai native cattle (White Lamphun and Ko Lan). The 1773–1790 bps of cloned Slc11a1 cDNA consisted of an open reading frame of 1,641 bps and 1,644 bps which coded for a complete protein of 547 and 548 amino acid residues. Hydrophobicity analysis of the encoded protein revealed 12 transmembrane regions. One predicted extracellular glycosylated loop, a consensus transport motif and several consensus phosphorylation sites were observed. At amino acid levels, Thai cattle Slc11a1 exhibited 99.3–99.8% and 99.3–100% identity with that of Zebu (Bos indicus) and European (Bos taurus) cattle, respectively. Six previously reported nucleotide substitution variants and one 3-nucleotide deletion variant within the coding region were identified. Genotyping of the (GT)n microsatellite polymorphism within the 3' UTR revealed three alleles (GT10 –GT12) in the GT block 1 and four alleles (GT13 –GT16) in the GT block 3. The data provide additional sequence information useful for further investigations on possible correlations between allelic variants of Slc11A1 gene and disease resistance in Thai cattle.